Antimicrobial Resistance Crisis and Combating Approaches - Alam, Mohammad Morshad; Islam, Muzahidul; Wahab, Abrar; Billah, Mamun (Journal of Medicine, 2019)
Antimicrobial resistance is a major global public health challenge threatening the utility of antibiotics. Inappropriate antibiotic prescribing and sales, using outside of the health sectors, and genetic factors are mainly influencing the development of antimicrobial resistance (AMR). Antibiotics abuse in human, wildlife, and farming practices have an enormous health impact. Recently approved antibiotics are anticipated to help stem this crisis. To fight against antibiotic resistance crisis, development of collaboration among concerned stakeholders to establish policies, initiatives, and investments for new agents can be auspicious. New methods of antibacterial drug identification and strategies, neutralize virulence factors, are the substitute approaches to address the AMR threat. Some novel approaches have also been taken to develop alternatives to typical antibiotics for bacterial infection. Here, we tried to highlight some of the key reasons behind antibiotic resistance, management, and burden. Moreover, this paper also discusses recent developments in this area and a brief overview of future antibacterial agents. J MEDICINE JUL 2019; 20 (1) : 38-45